Perilaku Pencarian Informasi Kesehatan di Internet pada Ibu Rumah Tangga Desa Tawangrejo Kabupaten Blitar - Fitria, Ria; Prajawinanti, Arin (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2022)
Information has become the main need of people's lives. The search for information related to health has recently become important for life, because with information a person can avoid being exposed to dangerous diseases. The type of research used is a qualitative approach with a descriptive method. Data was collected through observation, interviews, and literature study. This study uses the theory of information seeking behavior developed by Wilson in 2000. This study uses several informants who have the following categories; actively use the internet, have children, and search for health-related information. The results of this study indicate that the search for information begins with the need for information so that they can search for information, to reach the stage of using information, housewives seek information from various sources to determine the validity of an information. There are obstacles faced by housewives in the information search process, including not many media used to search for information, so that the information searched shows few references because it is only in one media. So in the process of searching for information, the housewives of Tawangrejo Village already have the ability to select information.